2014
DOI: 10.22219/jmb.v2i2.1705
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Konflik Peran Ganda Dan Stress Kerja Terhadap Kinerja Dosen Wanita Di Fakultas Ekonomi Universitas Jambi

Abstract: Sry RositaUniversitas Negeri JambiE-mail: sryrosita@gmail.comABSTRACTWork and family is two Women’s responsibilities Lecturer in the Faculty of Economics, University ofJambi, or often referred to as a dual role. Conditions such as the above can lead to a dual roleconflict which if left unchecked can lead to job stress in daily life and can lead to poor performancein particular women Lecturer in the Faculty of Economics University of Edinburgh. Stress is a naturalstate for human beings formed as a response to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
4
0
7
Order By: Relevance
“…Performance is what employees do, performance affects how much they contribute to the organization (Rosita, 2014). According to Lengkong et al 2019Performance is a description of the level of achievement of the implementation of an activity program or policy in realizing the goals, objectives, vision, and mission of the organization as outlined in the strategic planning of an organization.…”
Section: Employee Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Performance is what employees do, performance affects how much they contribute to the organization (Rosita, 2014). According to Lengkong et al 2019Performance is a description of the level of achievement of the implementation of an activity program or policy in realizing the goals, objectives, vision, and mission of the organization as outlined in the strategic planning of an organization.…”
Section: Employee Performancementioning
confidence: 99%
“…With the results of research showing that multiple roles have a positive and significant effect, this supports research conducted by Rahmadita (2013) which found that multiple roles have a positive and significant effect on the performance of female employees. Research conducted by Rosita (2014) found that multiple roles have a positive and significant effect on female employee performance. Research conducted by Ismiati (2019) and Wahab et al (2019) found that multiple roles have a positive and significant effect on the performance of female employees.…”
Section: The Influence Of Multiple Roles On the Performance Of Femalementioning
confidence: 99%
See 2 more Smart Citations
“…Rosita, 2014) menunjukkan bahwa Konflik peran ganda dan stres kerja baik secara simultan maupun parsial berpengaruh signifikan terhadap kinerja dosen wanita pada univeritas Jambi. Sementara itu, dalam penelitian menemukan bahwa work family conflict berpengaruh negatif terhadap kinerja karyawan di Restoran The Duck King Imperial Chef Galaxy Mall, dan stres kerja tidak berpengaruh signifikan terhadap kinerja karyawan di Restoran The Duck King Imperial Chef Galaxy Mall.…”
unclassified